Tailored SrFeO3-δ for chemical looping dry reforming of methane - Ao Zhu; Dongfang Li; Tao Zhu; Xing Zhu (Green Chemical Engineering)
Chemical looping dry reforming of methane (CL-DRM) is a highly efficient process that converts two major greenhouse gases (CH4 and CO2) into syngas ready for the feedstock of liquid fuel production. One of the major obstacles facing this technology now is creating oxygen carriers that are stable and reactive. We fabricated high-performance Sr0.98Fe0.7Co0.3O3-δ perovskite-structured oxygen carrier by combining A-site defects and B-site doping of SrFeO3-δ. During isothermal CL-DRM tests at 850 °C, Sr0.98Fe0.7Co0.3O3-δ achieved 87% CH4 conversion and 94% CO selectivity in the CH4 partial oxidation reaction, followed by a syngas yield of 8.5 mmol/g, and CO yield of 4.2 mmol/g in CO2 decomposition. A-site defect engineering of the perovskite creates abundant oxygen vacancies and enhances oxygen storage capacity (OSC). Co-doping of the B-site of Sr0.98FeO3-δ increases oxygen mobility and CH4/CO2 activation, resulting in high activity in the CL-DRM process. This methodology resulted in high ionic mobility and facilitated the rapid diffusion of oxygen in the bulk phase, thereby increasing the redox properties of SrFeO3-δ. The oxygen carrier exhibits excellent structural stability and regeneration ability in successive redox cycles. This strategy offers a simple but very effective pathway to tailor OSC, oxygen mobility, and oxygen vacancies of perovskite-structured materials for chemical looping or redox-involved processes.